Prognostic impact of cavotricuspid isthmus ablation for typical atrial flutter in patients with heart failure and reduced ejection fraction. (3rd October 2022) - Boxhammer, E; Bellamine, M; Szendey, I; Kletzer, J; Foresti, M; Kraus, J; Danmayr, F; Topf, A; Jirak, P; Bonsels, M; Lichtenauer, M; Hoppe, U C; et al.
Abstract: Background: The CASTLE-AF trial in 2018, showed that pulmonary vein isolation provides a survival benefit and a reduced hospitalization rate in patients with heart failure and concomitant atrial fibrillation. Typical atrial flutter (AFL) can also induce heart failure (tachymyopathy) or, if cardiomyopathy of other origin is prevalent, can further worsen it. Cavotricuspid isthmus ablation (CTI) is a simple, invasive electrophysiological procedure that can effectively treat AFL. Prognostic data on the impact of CTI in patients with heart failure and reduced ejection fraction (HFrEF) is lacking. Purpose: This study focused on the analysis of the clinical impact of CTI vs. medical therapy in patients with HFrEF. Methods: The present retrospective, international, multi-center study included 104 patients <85 years with AFL and heart failure (LVEF <50%). 64 patients underwent an electrophysiological study with successful CTI (ablation group), whereas 40 patients received medical therapy alone with frequency or rhythm control and guideline-compliant heart failure therapy (medical therapy group). Patients were followed up for a total of 2 years, with particular emphasis on recording the change in LVEF over time. The primary endpoints were cardiovascular mortality and hospitalization for cardiac causes. Results: Patients after CTI showed a significant increase in LVEF after 1 year (with the exception of valvular cardiomyopathy). The optimization of LVEF was also reflected in the Kaplan-Meier curves, as the ablation group had a significantly lower 2-year, cardiovascular mortality (p<0.001). The hospitalization rate for cardiac causes in the overall cohort showed a tendency towards reduced hospitalizations (p=0.072). Elderly patients also benefited from CTI in this study. Specifically, Patients ≥70 years of age showed a significantly lower re-hospialization rate after CTI (p=0.043) as well as a significantly reduced mortality after 2 years (p=0.012). Conclusions: CTI in patients with AFL and HFrEF was associated with significant optimization of LVEF and lower rates of hospitalization and mortality after 2 years. Patient age should not be a primary exclusion criterion for CTI because in this study, patients ≥70 years also benefited significantly from intervention in terms of mortality and hospitalization. Funding Acknowledgement: Type of funding sources: None.